Population pharmacokinetic analysis of tramadol and O -desmethyltramadol with genetic polymorphism of CYP2D6 - Lee, Joomi; Yoo, Hee-Doo; Bae, Jung-Woo; Lee, Sooyeun; Shin, Kwang-Hee (Drug design, development and therapy, 2019)
Tramadol is widely used to treat acute, chronic, and neuropathic pain. Its primary active metabolite, desmethyltramadol (M1), is mainly responsible for its µ-opioid receptor-related analgesic effect. Tramadol is metabolized to M1 mainly by the cytochrome P450 (CYP) 2D6 enzyme, and to other metabolites by CYP3A4 and CYP2B6. The aim of this study was to develop a population pharmacokinetic (PK) model of tramadol and its metabolite using healthy Korean subjects. Data on plasma concentrations of tramadol and M1 were obtained from 23 healthy Korean male subjects after a twice-daily oral dose of 100 mg of tramadol, every 12 hrs, for a total of 5 times. Blood samples were collected at 0 (pre-dose), 0.5, 1, 1.5, 2, 2.5, 3, 4, 6, 8, 10, 12, 24, 48 and 72 hrs after last administration. Plasma tramadol concentrations were then analyzed using LC/MS. Population PK analysis of tramadol and its metabolite was performed using a nonlinear mixed-effects modeling (NONMEM). A one-compartment model with combined first-order and zero-order absorption was well fitted to the concentration-time curve of tramadol. M1 was well described by the one-compartment model as an extension of the parent drug (tramadol) model. Genetic polymorphisms of correlated with the clearance of tramadol, and clearance from the central compartment to the metabolite compartment. The parent-metabolite model successfully characterized the PK of tramadol and its metabolite M1 in healthy Korean male subjects. These results could be applied to evaluate plasma tramadol concentrations after various dosing regimens.